2023
DOI: 10.1038/s41598-023-31554-3
|View full text |Cite
|
Sign up to set email alerts
|

High-precision spatial analysis of mouse courtship vocalization behavior reveals sex and strain differences

Abstract: Mice display a wide repertoire of vocalizations that varies with sex, strain, and context. Especially during social interaction, including sexually motivated dyadic interaction, mice emit sequences of ultrasonic vocalizations (USVs) of high complexity. As animals of both sexes vocalize, a reliable attribution of USVs to their emitter is essential. The state-of-the-art in sound localization for USVs in 2D allows spatial localization at a resolution of multiple centimeters. However, animals interact at closer ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…Next, we validated that the separation of USVs according to the emitter was precise, even during close contact between the animals, a condition in which previous studies struggled to properly separate vocalizations made by freely interacting animals 1921 . For this, we analyzed all video files using TrackRodent software 28 and extracted all time epochs in which the subject animal either physically contacted the stimulus animal during free interaction (Fig.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…Next, we validated that the separation of USVs according to the emitter was precise, even during close contact between the animals, a condition in which previous studies struggled to properly separate vocalizations made by freely interacting animals 1921 . For this, we analyzed all video files using TrackRodent software 28 and extracted all time epochs in which the subject animal either physically contacted the stimulus animal during free interaction (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…This arrangement, however, restricts the types of interaction between animals and does not allow them to freely contact each other. Other studies combined an array of microphones around the arena and performed computational analysis of the various signals to decide which animal emitted a given USV 1921 . The efficiency of this technique was limited to cases where the heads of the animals were distant from each other by several centimeters (up to ∼1.5 cm with accuracy of 84.3% 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, it remains open how well vocalizations can be separated from the five stationary microphones alone. In groups of mice and using microphone arrays and a camera, it has been shown that vocalizations can be assigned to individual animals by combining sound source localization and animal position tracking 41 . But because of frequent vocal jamming in songbirds, we doubt these approaches will make the use of animal-borne transmitters obsolete in song-learning studies to be performed in the BirdPark where subtle song changes need to be tracked in developmental time.…”
Section: Discussionmentioning
confidence: 99%